AI adoption in schools global trends, benefits, and challenges - English, Vincent (International Journal of Educational Technology and Learning, 2025)
Artificial Intelligence (AI) is rapidly transforming education globally, presenting both unprecedented opportunities and complex challenges. This academic paper synthesises contemporary research and recent developments to provide a comprehensive overview of AI adoption in schools, spanning from primary to higher education. It meticulously examines the global trends driving AI integration, elucidates its multifaceted benefits, and critically analyses the significant challenges and ethical considerations that accompany its implementation. Furthermore, this paper examines contrasting national approaches, specifically comparing Ireland’s cautious, deliberative stance with Estonia’s proactive, systemic "AI Leap" strategy. Through this comparative analysis, the paper aims to illustrate the diverse pathways nations are taking in integrating AI into their educational systems, offering insights into effective strategies and potential pitfalls for policymakers, educators, and technology developers worldwide.